Internet peer production and unauthorized copying of intellectual property via BitTorrent network - Slawomir Czetwertynski (Institute of Economic Research (IER), 2015)
This article refers to the phenomenon of peer production in the context of unauthorized copying of information goods. Peer production as says Yochai Benkler is production based on activity of community. It is widely used on the Internet and in its effect there have been created and developed such information goods as GNU Linux and Wikipedia. Although peer production contributes to the growing importance of free software or open source initiative, it is also strongly associated with the spread of unauthorized copying of intellectual property commonly know as Internet piracy. The mass character of this phenomenon - nearly 24% of Internet traffic is unauthorized - can not be underestimated. The hypothesis stands in the article is that a low level of protection against the production of unauthorized copies of intellectual property stems from the fact that they are formed largely in the process of peer production. The objective of the study is to verify this hypothesis in the context of the nature of peer production and unauthorized copying. The research area is limited to file-sharing networks P2P protocol based on BitTorret.
Keywords: D01; D24; O34; 330; peer production; unauthorized copying; intelecttual property; BitTorrent